A step-wise synthetic approach is necessary to access γ-conjugates of folate: folate-conjugated prodigiosenes. Issue 25 (7th May 2019) - Figliola, Carlotta; Marchal, Estelle; Groves, Brandon R.; Thompson, Alison
Abstract : Despite the vast literature that describes reacting folic acid with a pharmacophore, this route is ineffective in providing the correct regioisomer of the resulting conjugate. Abstract : Despite the vast literature that describes reacting folic acid with a pharmacophore, this route is ineffective in providing the correct regioisomer of the resulting conjugate. We herein present a step-wise route to the preparation of nine folate conjugates of the tripyrrolic prodigiosene skeleton. The strict requirement for step-wise construction of the folate core is demonstrated, so as to achieve conjugation at only the desired γ-carboxylic acid and thus maintain the α-carboxylic site for folate receptor (FRα) recognition. Linkages via ethylenediamine, polyethylene glycol and glutathione are demonstrated.